Long-term surgical outcomes of Non alcoholic fatty liver disease associated hepatocellular carcinoma. (May 2022) - D'Silva, Mizelle; Cho, Jai Young; Han, Ho-Seong; Yoon, Yoo-Seok; Lee, Hae Won; Lee, Jun Suh; Lee, Boram; Kim, Moonhwan
Abstract: Background: The global burden of non-alcoholic fatty liver disease (NAFLD) and NAFLD-associated hepatocellular carcinoma (HCC) is steadily rising. We pursued to investigate the results after liver resection for NAFLD-HCC versus hepatitis B virus (HBV)-HCC exploiting Kaplan Meier method, log-rank test and uni/multivariate analysis with the logistic regression models". Methods: Patients who underwent liver resection for HCC between January 2004 and December 2018 were included. The outcomes of NAFLD-associated HCC were analyzed. Results: The prevalence of NAFLD-associated HCC was 8.4%. A significant number of NAFLD patients had no cirrhosis (21 patients; 38.8%). Although NAFLD patients had a significantly better 5-year survival ( P  = 0.033), NAFLD was not significantly associated with overall survival in multivariate analysis ( P  = 0.287). However, survival after 5 years declined in NAFLD patients and was similar to HBV. NAFLD was protective against systemic recurrence compared with HBV ( P  = 0.018), and this was confirmed in multivariate analysis ( P  = 0.044). Five-year systemic recurrence ( P  = 0.044) was significantly lower in NAFLD patients and decreased with time from surgery. Multivariate analysis revealed that anatomical liver resection was independently associated with decreased recurrence in NAFLD patients (HR = 0.337; P  = 0.033). Conclusion: Overall survival is similar between NAFLD-associated HCC and HBV-associated HCC. Despite there being no significant difference between liver function tests, type of surgery performed, liver cirrhosis, size of tumor, number of tumors, pathological factors like satellite nodules and Edmonson Steiner staging, NAFLD-associated HCC shows lower systemic recurrence compared to HBV-associated HCC. Graphical abstract: Image 1 Highlights: As the global burden of NAFLD rises, factors affecting survival of HCC patients associated with NAFLD must be assessed. NAFLD patients had a significantly better 5-year survival and NAFLD was protective against systemic recurrence compared with HBV. Anatomical liver resection was the only factor independently associated with decreased recurrence in NAFLD patients. Optimal long term outcomes are possible with appropriate, timely surgical management of NAFLD-associated HCC.